Pengaruh Return On Asset, Tingkat Inflasi, Suku Bunga dan Debt to Equity Ratio terhadap Harga Saham - Asmara, Derita; Yamasitha, Yamasitha; Anggraini, Dian (Jurnal Ekonomi & Bisnis, 2024)
The inflation rate is the most powerful macroeconomic variable and is recognized by economic actors, because it can have a negative influence on the structure of production costs and welfare levels. Interest rates are a significant variable in a country's trade because interest rates influence trade as usual. Debt To Equity Ratio is also known as a ratio that looks at a company's debt, which is obtained from total debt divided into total assets. The lower the better because it is safe for creditors during liquidation. Share price is the capital market price and is one of the indicators that must always be monitored in the company. This research aims to analyze and estimate the influence of ROA, inflation rate, interest rate and DER on share prices in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The population consists of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022, namely 214 companies with a total sample of 63 companies using purposive sampling. The research design used was quantitative by collecting secondary data. The data analysis technique is in the form of multiple linear regression analysis using IMB SPSS 25. The results of the research using the t test found that ROA, inflation and DER partially have a positive effect on stock prices, interest rates have no and significant effect on stock prices. Simultaneously Return On Assets, Inflation Rate, Interest Rates and Debt To Equity Ratio have a significant effect on share prices in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. It is hoped that the results of this research can provide information as a basis for consideration, support and contribution of thought to future researchers in order to improve opinions in conducting research.